2009
DOI: 10.1007/s11116-009-9224-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring public transport usage trends in an ageing population

Abstract: Travel behaviour, Public transport, Elderly, Travel, Trends,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 19 publications
2
42
0
Order By: Relevance
“…In recent years, studies have begun to add the factor of season and explore its impact on the elderly's travel behavior. Regarding individual attributes, existing studies have demonstrated that gender, employment status, driver's license, educational level, and ethnicity have significant effects on senior citizens' travel behavior [13][14][15][16]. Some studies have suggested that women and the unemployed elderly travel a shorter distance and are less likely to travel and that women are more reliant on public transport [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, studies have begun to add the factor of season and explore its impact on the elderly's travel behavior. Regarding individual attributes, existing studies have demonstrated that gender, employment status, driver's license, educational level, and ethnicity have significant effects on senior citizens' travel behavior [13][14][15][16]. Some studies have suggested that women and the unemployed elderly travel a shorter distance and are less likely to travel and that women are more reliant on public transport [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While issues related to mobility exist within the senior population due to reduced cognitive abilities and increased medical issues or disabilities, there are indications that today's senior population is healthier and possesses more disposable income than their previous senior cohort (Currie and Delbosc, 2010;Cutler, 2001). Due to the increasing size, overall wealth, and life expectancy of the senior population, advancements in personal mobility will inevitably become more important.…”
Section: Introductionmentioning
confidence: 99%
“…More than 40 per cent considered that it was very likely or likely they would be using public transport. An Australian longitudinal study among "baby boomers" (born 1945-54) showed a small trend towards an increase in public transport use (Currie and Delbosc, 2010). The authors state that the future for public transport is not as bleak as research has previously shown but that the public transport system and urban density is of great importance for how public transport is used and valued among residents.…”
Section: Older People's Travel Activitiesmentioning
confidence: 89%